Pembelajaran Dan Pengembangan Pendidikan Fisik Untuk Mahasiswa - Rindu Dameria Purba; Febrianto Sianturi; Muhammad Idris; Radot Sihombing; Haris Alfarisi; Nurkadri Nurkadri (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Learning is the process of instructing students to utilize educational ideas and theories as a major factor in academic performance. Physical education is a powerful tool for the education of children. It is an essential component of obtaining a high quality education and part of lifelong learning. Physical education encourages the development of motor skills, physical talents, knowledge and reasoning, appreciation of values (attitude, mental-emotional-religious and social), as well as habituation of healthy lifestyles in order to encourage balanced growth and development. Nothing is complete without physical education, and there is no such thing as good physical education without the concept of learning that is full of discovery and improvisation, and a teacher carries out his duties as a teacher. Learning also requires physical education instructors to be truly successful in carrying out their responsibilities to provide high and quality education, especially in terms of time management during the learning process